Organisational Culture and Its Social Impact on Employee Commitment and Performance in Hyderabad Information Technology Companies - Nandhini, Dr. B.; Sindhu, Dr.G. (South Eastern European Journal of Public Health, 2025)
The article seeks to explore how the above cultural dimensions influence the emotional commitment, job contentment and performance of the workers in the cut throat IT industry. The study also examines relevant cultural factors including communication management, management of innovation, reward management, and leadership endorsement to bring about improvement in culture commitment and performance. The work therefore adopted a quantitative research design and the selection of 300 IT employees from Hyderabad. For respondents’ selection, convenience sampling was employed to acquire responses because of constraints in time and resources. Questionnaire was developed through the existing literature on organizational culture, employee commitment and performance. Future research could extend farther the focus of the study to other industries and other regions to encompass a broad range of Organization culture and Employee commitment and how this influences performance. The results of this study offer valuable visions for HR practitioners and leaders in IT companies. Through fostering a strong, inclusive, and adaptable organizational culture, companies can enhance employee commitment and performance, ultimately achieving long-term success in a highly competitive sector. Additionally, this study underscores the importance of investing in cultural alignment and social cohesion as integral components of employee engagement strategies.